In Search of Critical Thinking in Psychology: An Exploration of Student and Lecturer Understandings in Higher Education. (September 2013) - Duro, Elaine; Elander, James; Maratos, Frances A.; Stupple, Edward J.N.; Aubeeluck, Aimee
This qualitative study of understandings of critical thinking in higher education aimed to identify themes that could help to demystify critical thinking and inform its more explicit incorporation in the psychology curriculum. Data collected from focus groups with 26 undergraduate psychology students and individual semistructured interviews with 4 psychology lecturers were examined using thematic analysis. The same key themes were identified from both student and lecturer data: 'vague beginnings', 'conceptualizations', 'development and transitions', and 'learning strategies'. Both students and lecturers described critical thinking as implicit knowledge that develops through social interactions. The findings indicate the importance of explicit discussion about critical thinking, and could be used to inform the design and delivery of instructional methods to promote critical thinking.